PENGARUH KEPEMIMPINAN, INSENTIF, DAN MOTIVASIPADA KINERJA PEGAWAI BIDANG AKUNTANSI(STUDI PADA PEMERINTAH KABUPATEN BULELENG). - Ida Bagus Gde Adi Manubawa; I Gusti Ayu Novitasari; Ni Made Galih Masari; I Ketut Merta (Jurnal Ilmiah Satyagraha, 2025)
Abstract Purpose: This research seeks to examine the impact of leadership, incentives, and motivation on the performance of accounting staff in the Government of Buleleng Regency. Method research: The research employs a quantitative approach using nonprobability sampling, specifically purposive sampling. The data were obtained through questionnaires distributed to 40 accounting employees across various Regional Government Organizations (OPD) in Buleleng Regency. The collected data were then analyzed using multiple linear regression with the assistance of SPSS version 25 software. Result: The findings of the study indicate that leadership, incentives, and motivation have a positive and significant impact on employee performance, both individually and simultaneously. This demonstrates that good leadership, appropriate incentive schemes, and high motivation contribute to increased employee productivity and performance. Limitations: However, the study is not without limitations, as it is based on a relatively small sample size and its focus on a single regency. Contribution: Nonetheless, the study's findings offer valuable contributions to the domains of accounting, human resource management, and public administration, particularly in the context of enhancing government employee management strategies. Moreover, the research serves as a valuable reference for local governments in formulating policies aimed at enhancing employee performance through the implementation of effective leadership, appropriate incentives, and motivation. Keywords: leadership, incentives, motivation, employee performance, local government.